Nikolai, the only bear - Joosse, Barbara M.; Liwska, Renata (New York : Philomel Books, 2005)
Nikolai, a bear who lives in the orphanage in Novosibirsk, Russia, does not seem to fit in until the day some visitors arrive from America.
Keywords: Orphans -- Fiction; Orphanages -- Fiction; Bears -- Fiction; Orphans -- Juvenile fiction; Orphanages -- Juvenile fiction; Bears -- Juvenile fiction; Novosibirsk (Russia) -- Fiction; Russia -- Fiction; Novosibirsk (Russia) -- Juvenile fiction; Russia -- Juvenile fiction